The Impact of the Australian Carbon Tax on Industries and Households. (February 2014) - Meng, Sam; Siriwardana, Mahinda; McNeill, Judith
With the new Australian Government and various interest groups objecting to the Australian carbon tax, public opinion about pricing carbon is divided. Some of the disagreement may be due to misunderstandings about the effects of the policy. In an effort to clarify some of the issues, this article reports the simulated effects of a carbon tax of A$23 per tonne of carbon dioxide on different economic agents, with and without a compensation policy. We employ a computable general equilibrium (CGE) model with an environmentally extended social accounting matrix (SAM). At the sectoral level, brown coal electricity, black coal electricity and the brown coal mining sectors are big losers. The effect on various employment occupations is mildly negative, ranging from −0.6 per cent to −1.7 per cent, with production and transport workers worst affected. According to household utility projections, low-income households suffer more from a carbon tax and benefit more from the proposed compensation policy. However, the commonly used equivalent variation (EV) tends to reverse this conclusion. JEL Classification: H23, H31, H32, Q52, Q54